Auxetic tubular scaffolds via melt electrowriting. (August 2020) - Paxton, Naomi C.; Daley, Ryan; Forrestal, David P.; Allenby, Mark C.; Woodruff, Maria A.
Abstract: Auxetics are an interesting class of materials that expand in transverse directions when tensile loading is applied. For example, in contrast to conventional materials, an auxetic tube will increase in diameter when stretched along its axis. To date, auxetic tubular scaffolds have been proposed for applications in tissue engineering and soft robotics; however, they have not yet been routinely produced in precisely-engineered microfibre structures using the melt electrowriting additive manufacturing method. Using a custom melt electrowriting device and rotating mandrel collector, scaffolds with a re-entrant honeycomb unit cell pattern were designed and fabricated from polycaprolactone microfibres. These scaffolds were tensile tested to characterise their auxetic properties compared to traditional crosshatch-patterned tubular scaffolds. The auxetic scaffolds exhibited an increase in diameter up to 80.8%, as predicted from the unit cell pattern at maximum strain of 14.1%, resulting in a Poisson's ratio of −5.8. By comparison, crosshatch scaffolds exhibited a similar stress-strain profile to the auxetic tubular scaffold with identical pore size, however significant radial compression was observed leading to a Poisson's ratio of +5.7. This study reports the design and fabrication of auxetic tubular microfibre scaffolds fabricated via melt electrowriting for the first time and offers a versatile fibre patterning system towards applications in biofabrication and robotics. Graphical abstract: Unlabelled Image